The Effect of Dividend Pershare on Stock Prices at State-Owned Banks - Ana Sakinatun Nisa; Mira Rahmawati; Dim Zarita Suryanugraha; Prahita Sri Rahayuningrat (Jurnal Inovasi Bisnis dan Kewirausahaan, 2025)
The purpose of this study was to determine empirical evidence about the effect of dividend per share on stock prices. The data used in the study is based on State-Owned Banks listed on the Indonesia Stock Exchange in the 2019-2024 period. The data analysis technique uses multiple regression analysis. Sampling was carried out using purposive sampling method which then obtained 5 sample companies. The analysis technique used in this research is Statistical Package for the Social Sciences (SPSS). The results in this study indicate that dividend per share shows a significant positive effect on stock prices. So the greater the dividend distributed to shareholders, the greater the effect on the share price. Dividend payments often depend on the company's share price. However, dividend payments are one of the most challenging topics in modern financial economics. Years of research have not been able to resolve it. Research on dividend payments has shown that, not only the general theory of dividend payments remains elusive, but also corporate dividend practices vary over time between companies and between countries.